Pengaruh Faktor-faktor Perilaku Konsumen Generasi Z Terhadap Keputusan Pembelian Produk Jamu Herbal di PT. Bhineka Rahsa Nusantara - Nucifera, Yasmin Hartika; Nugraha, Adi (Universitas Galuh, 2024)
Jamu, a traditional Indonesian beverage, embodies local wisdom that warrants preservation. The current emphasis should be placed on the younger generation, particularly Generation Z, by herbal medicine enterprises, as they represent significant potential for the industry. However, introducing herbal medicine as a healthy lifestyle choice for Gen Z proves challenging. Hence, this research aims to identify factors influencing Gen Z’s decision-making regarding herbal medicine consumption. By doing so, it seeks to devise effective marketing strategies tailored to Gen Z consumers. The study was conducted at PT. Bhineka Rahsa Nusantara in Bandung City, utilized a quantitative research design. Data collection involved distributing questionnaires to 61 Gen Z consumers and employing path analysis using Smart-PLS4 for statistical analysis. The findings reveal that consumer behavior factors, including cultural, social, and personality factors, significantly influence purchasing decisions. These factors collectively account for 64% of the influence, while the remaining 36% is attributed to other unexamined factors. Among these factors, cultural considerations emerge as the most influential, affecting Gen Z’s purchasing decisions by 27,29%, followed by social factors at 18,6%, and personality factors at 18,07%.